Changes in transferrin gene expression in sea bass (Dicentrarchus labrax) challenged with Vibrio anguillarum - Ercan, Menekse Didem; Karatas, Suheyla; Turgay, Emre; Kolukirik, Mustafa; Ince, Orhan; Ince, Bahar (The Scientific and Technological Research Council of Turkey (TUBITAK-ULAKBIM) - DIGITAL COMMONS JOURNALS, 2013)
Vibrio anguillarum expresses several virulence factors and causes hemorrhagic septicemia accompanied by serious losses in marine fish. Transferrin is a glycoprotein, also known as a multitasking protein, which is mainly synthesized by the liver. It has a fundamental role in the immune system. In the present study, the transferrin gene expression of sea bass (Dicentrarchus labrax) was investigated during an experimental infection with V. anguillarum. Fish samples were examined by hematological and serological methods as well as real-time polymerase chain reaction. The infection was performed via water. The sampled fish displayed vibriosis infection symptoms, both internally and externally. The transferrin saturation in the diseased fish serum decreased dramatically and the transferrin gene expression increased during the first 2 days; however, it decreased in the subsequent days.